The Dubbing of Gay-themed TV Series in Italy: Corpus-based Evidence of Manipulation and Censorship (Altre Modernità, 2016)
The manipulation and censorship of taboo and sensitive references in AVT has attracted the interest of several scholars over the last few years, but systematic studies of the impact of such practices on different genres in different countries are still needed. The paper analyses the Italian dubbing of three gay-themed TV series, Queer as Folk, Queer as Folk (US remake), and The L Word. Gay-themed series are less mainstream on Italian TV channels than in the UK and the USA, and gayspeak as a linguistic phenomenon is not well-known to Italian audiences. Consequently, the Italian dubbed dialogues are the product of different degrees of manipulation and even censorship. The paper finds empirical evidence of such alterations in data from the DubTalk corpus and attempts a tentative evaluation of the impact of such practices on the Italian versions of the above-mentioned series.
Keywords: dubbing; corpus; TV series; gayspeak; censorship; manipulation